RELIABILITY-BASED DESIGN PROCEDURE OF AXIALLY LOADED PILES (Journal of Engineering, 2010)
Geotechnical engineering involves many different and complex materials and many different mechanisms of behaviour. The direct use of experience as a guide to the prediction and design is effective provided these are understood. Geotechnical engineering is a relatively new science. Its successful application to prediction requires realistic assumptions to be made, and predictions must be tested against reality. Methods of prediction need then to be refined. An example of the importance of making realistic assumptions is examined in this paper. It includes the effects of soil properties on the ultimate capacity of axially loaded piles.Better analysis offers better prediction and better understanding. Both are only possible when reality is modelled. There are occasions when mechanisms are too complex for predictive analysis. Prediction must then be based directly on experience, applied with an understanding of the mechanisms involved. Moreover, methods of analysis may become too sophisticated for everyday use. However, pseudo-analysis, involving standardized methods based on oversimplified and unrealistic mechanisms of behaviour and material properties, is dangerous. The use of engineering experience as a guide to prediction and design may offer a more effective alternative, provided it is based on a realistic understanding of mechanisms and materials.In this paper, a procedure is recommended to estimate the bearing capacity of axially loaded piles based on reliability calculations. The procedure is an extension of the point estimate method in which the expected values of the standard deviation of the capacity and demand functions are calculated. The probability of failure, the reliability, central factor of safety and reliability index are calculated as appropriate. The procedure is then applied to two cases where the pile in the first case is driven in sand while in the second, it is driven in clay.